2018
DOI: 10.3390/ijerph15061139
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Nutrition Promotion in Private Secondary Schools in Kolkata, India: Perspectives of Parents and Teachers

Abstract: School-based nutrition promotion is critical to the development of healthy eating habits in adolescents. Unfortunately, most Indian secondary schools do not support healthy eating among adolescents. Therefore, this study was designed to understand the perspectives of teachers and parents regarding the potential barriers to nutrition promotion in Indian secondary schools. Thirty-two teachers and 280 parents from five private English-speaking secondary schools in Kolkata, India took part in a cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
(80 reference statements)
4
21
0
Order By: Relevance
“…Consistent with previous research in this space, this study has shown that strong school food policymaking requires committed advocates at all levels, especially within the school community (22,24,68). Our study and others (71,80,81) have shown that actors responsible for implementation generally have a strong interest in the wellbeing of children, but that this does not necessarily translate to policy compliance by those actors (71).…”
Section: Capitalising On Commitment From Political and Community Leaderssupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with previous research in this space, this study has shown that strong school food policymaking requires committed advocates at all levels, especially within the school community (22,24,68). Our study and others (71,80,81) have shown that actors responsible for implementation generally have a strong interest in the wellbeing of children, but that this does not necessarily translate to policy compliance by those actors (71).…”
Section: Capitalising On Commitment From Political and Community Leaderssupporting
confidence: 86%
“…The relative expense of healthy food, and a perceived lack of nancial viability for implementing school nutrition standards, are frequently reported as barriers to the implementation of school food policies (21)(22)(23). The lack of understanding of healthy food provision and school food standards, and absence of the requisite knowledge and skills to execute them is common among school-based vendors (17,19,20,22,24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, private school students make up about 40 percent of Indian secondary students [ 32 ]. Methodological details for this survey have also been reported previously [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that strong school food policymaking requires committed advocates at all levels, especially within the school community (20,22,66). Developing a common purpose and building a sense of responsibility among school-level stakeholders is critical to improve implementation of school food policies (17).…”
Section: Capitalising On Commitment From Political and Community Leadersmentioning
confidence: 99%
“…The relative expense of healthy food, and a perceived lack of financial viability for implementing school nutrition standards, are frequently reported as barriers to the implementation of school food policies (19)(20)(21). The lack of understanding of healthy food provision and school food standards, and absence of the requisite knowledge and skills to execute them is common among school-based vendors (15,17,18,20,22,23). Additionally, the multisectoral nature of food policies can often lead to dispersed implementation and governance arrangements (24,25).…”
Section: Introductionmentioning
confidence: 99%